O conhecimento na intervenção do(a) assistente social: as influências da sociedade capitalista na apropriação e uso do conhecimento teórico - Caleffi, Hígor (2013)
This dissertation aims to discuss and analyze the theoretical knowledge sought by social workers to understand the reality and professional intervention offered by the institution and employer. Problematize the theoretical knowledge acquired through professional social work contributes to thinking skills necessary for the unveiling and intervention in social issues, know the context in which it operates and the influences exerted by capitalist society and the ideologies of the employing institution